Opposite Responses of Native and Nonnative Birds to Socioeconomics in a Latin American City - Nélida R. Villaseñor; Catalina B. Muñoz-Pacheco; Martín A. H. Escobar (Animals, 2024)
Due to the massive increase of the urban population, a global target is to achieve sustainable cities that are sensitive to nature and environmentally just for urban dwellers. To accomplish this, it is important to understand the responses of native and nonnative birds, identify the environmental variables that promote native species and limit nonnative species, and understand how they vary among socioeconomic groups. Although many cities in the Global South exhibit strong social and environmental segregation, few studies have investigated the relationship between socioeconomics and biodiversity. Therefore, to help promote ecological justice and biodiversity conservation in the developing world, we investigated the influence of socioeconomic level and woody cover on bird species richness and abundance in the city of Santiago de Chile. We also investigated whether bird response changes with species provenance—it is important to understand the response of native birds separately from nonnative birds because they imply opposite management strategies (e.g., conservation vs. species control/eradication). Thus, we surveyed 120 sites located in residential areas of high, medium, and low socioeconomic levels across the city and fit generalized linear (mixed) models that described bird species richness and abundance for total, native, and nonnative birds according to socioeconomic level and woody vegetation cover. We found that both socioeconomic level and woody vegetation cover influenced the bird community, but their effects changed with bird species origin, having opposite effects on native and nonnative birds. Residential areas where wealthier people live supported greater species richness and abundance of native birds than residential areas where people of lower socioeconomic status live. In contrast, residential areas where vulnerable people live had greater bird abundance that was mainly composed of nonnative birds. Therefore, affluent neighborhoods provide more opportunities to encounter native birds and experience nature close to home than poorer neighborhoods. Due to woody cover having positive effects on native birds and a negative influence on nonnative birds, increasing tree and shrub cover will contribute to supporting more native birds in residential areas deprived of woody vegetation, which are commonly low socioeconomic areas. Additional variables that can explain bird response among residential areas of different socioeconomic levels need to be investigated to better understand the factors influencing the distribution of birds in cities and promote a more biodiverse and environmentally just city.